Obsessive-compulsive symptoms and personal recovery in patients with schizophrenia spectrum disorders: A cross-sectional study - Jelsma, Auke; Schirmbeck, Frederike; van der Pluijm, M.; Simons, C.; Vellinga, A.; de Koning, M.; de Haan, L. (Schizophrenia research, 2025)
Background - Obsessive-compulsive symptoms (OCS) frequently co-occur in patients with Schizophrenia Spectrum Disorders (SSD). Patients with SSD and OCS experience increased clinical and social challenges, including diminished quality of life and subjective well-being. However, it is unknown whether co-morbid OCS are associated with personal recovery. - Aim - To investigate whether the presence and severity of OCS in patients with SSD is associated with lower self-reported personal recovery. - Methods - A cross-sectional design was employed, examining 527 patients with SSD. Group comparisons between patients with and without OCS for self-reported personal recovery (assessed with the Recovery Assessment Scale (RAS-24)) were conducted using analysis of covariance, adjusting for positive, negative and general symptoms. Multiple regression analyses were performed in 133 patients with co-occurring OCS to assess the additional explained variance in personal recovery by OCS severity after adjusting for the same covariates in the first block of the model. - Results - Group comparisons demonstrated that the presence of co-morbid OCS was associated with lower scores in personal recovery. Multiple hierarchical regression analyses showed that OCS severity was significantly associated with personal recovery by explaining an additional 3.0 % of variance in personal recovery. - Conclusion - Our findings suggest that co-occurring OCS in patients with SSD are relevant for personal recovery and that treatment should also address OCS.
Gesehen am 22.09.2025